2016
DOI: 10.4038/tare.v19i2.5347
|View full text |Cite
|
Sign up to set email alerts
|

Tea small holders’ perceptions and experience with tea small holdings development societies (TSHDS) in Matara district of Sri Lanka

Abstract: Tea Small Holdings Development Societies (TSHDS) have been established under the guidance of Tea Small Holdings Development Authority (TSHDA) in Sri Lanka. These Societies were expected to act as bridges among the tea small holders and other relevant organizations including TSHDA and to provide necessary services to the tea small holders in effective and efficient way and to identify the tea small holders actual needs and opportunities through feedbacks. However, with all the reforms in the tea small holdings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, to enhance the status of these societies is prime important, and therefore, it is essential to study the success cases in smallholding sector in elsewhere and explore the possibility to adapt them into local condition. In fact, the study of Bandula et al (2016) found that 75 percent of the members as well as 85 percent of the nonmember in the study sample, were of the opinion that RTS could be transformed as a productive entity which can make an impact on their lives.…”
Section: Present Status Of Tsdsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, to enhance the status of these societies is prime important, and therefore, it is essential to study the success cases in smallholding sector in elsewhere and explore the possibility to adapt them into local condition. In fact, the study of Bandula et al (2016) found that 75 percent of the members as well as 85 percent of the nonmember in the study sample, were of the opinion that RTS could be transformed as a productive entity which can make an impact on their lives.…”
Section: Present Status Of Tsdsmentioning
confidence: 86%
“…Thus, their contribution to the national level in terms of the coverage is insignificant. Bandula et al (2016), has done a study to evaluate whether these societies were able to make any quantifiable impact on tea smallholders in Matara district. Their findings revealed that there was no significant improvement in tea smallholding sector in the study area as because of the introduction of TSHDSs.…”
Section: Tea Producers Cooperative and Fos Promoted By Agribusiness Entitiesmentioning
confidence: 99%
“…(P2D2)]. According to the study conducted in Matara district by Bandula et al,(2016) also found that considerable percentage of membership has less interest towards the RTS affairs. Perhaps, the interest of the members fluctuates over the times.…”
Section: Attitudes Of the Membershipmentioning
confidence: 97%
“…The technology utilization level and execution of development activities were found to be not at a satisfactory level (Mahindapala et al 2019a;Mahindapala et al, Mahindapala et al 2019b;Mahindapala et al 2019c;Mahindapala et al 2020a;TSHDA, 2010TSHDA, -2018. Further, a study done in the Matara district, revealed that the majority of TSDS members were of the opinion that no significant improvement in their living standards due to the introduction of the TSDSs (Bandula et al (2016).…”
Section: Introductionmentioning
confidence: 99%